Cosmic ray acceleration by a supernova shock in a dense circumstellar plasma - Bell, A (2008)
Cosmic ray acceleration may occur at a supernova shock expanding into a circumstellar wind sustaining a Parker spiral magnetic field. Cosmic rays drift to the poles producing a large cosmic ray pressure which can generate polar density cavities through which cosmic rays escape upstream of the shock. This may be relevant to gamma-ray bursts accompanying shock breakout. © 2008 The Author. Journal compilation © 2008 RAS.